COVID-19 in the global south : impacts and responses - Carmody, Pádraig Risteard; McCann, Gerard; Colleran, Clodagh; O'Halloran, Ciara (Rapid response., 2021)
Available Open Access under CC-BY-NC-ND licence. Bringing together a range of experts across various sectors, this important volume explores some of the key issues that have arisen in the Global South with the COVID-19 pandemic. Situating the worldwide health crisis within broader processes of globalisation, the book investigates implications for development and gender, as well as the effects on migration, climate change and economic inequality. Contributors consider how widespread and long-lasting responses to the pandemic should be, while paying particular attention to the accentuated risks faced by vulnerable populations. Providing answers that will be essential to development practitioners and policy makers, the book offers vital insights into how the impact of COVID-19 can be mitigated in some of the most challenging socio-economic contexts worldwide.